1987
DOI: 10.1246/cl.1987.635
|View full text |Cite
|
Sign up to set email alerts
|

High-Tc Superconducting Oxide Solid Solutions (La1−x(Ba,Sr,Ca)x)2CuO4−δ

Abstract: The system (La1−x(Ba,Sr,Ca)x)2CuO4−δ with x=0.1 has been found to be a high temperature superconducting phase in the entire compositional range of the three alkali earth cations. (La0.9Sr0.1)2CuO4−δ, displayed the highest critical temperature and the shortest distance for Cu–O bonds within the basal layer plane of the K2NiF4-type crystal structure, suggesting the two-dimensional nature of the conduction mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…R ock-salt structure LaO is recognized as an insulating block layer embedded in mother compounds of high-temperature superconducting layered perovskite cuprates (La,M) 2 CuO 4 (M = Ba, Sr). 1,2 On the other hand, lanthanum monoxide bulk polycrystal, synthesized several decades ago, has shown ordinary metallic conduction, 3,4 and further investigations have been scarcely seen, probably due to its poor chemical stability. Recently, various rare-earth monoxide epitaxial thin films have been synthesized through state-ofthe-art oxide thin-film epitaxy, unveiling unique electronic functionalities in rare-earth monoxides.…”
mentioning
confidence: 99%
“…R ock-salt structure LaO is recognized as an insulating block layer embedded in mother compounds of high-temperature superconducting layered perovskite cuprates (La,M) 2 CuO 4 (M = Ba, Sr). 1,2 On the other hand, lanthanum monoxide bulk polycrystal, synthesized several decades ago, has shown ordinary metallic conduction, 3,4 and further investigations have been scarcely seen, probably due to its poor chemical stability. Recently, various rare-earth monoxide epitaxial thin films have been synthesized through state-ofthe-art oxide thin-film epitaxy, unveiling unique electronic functionalities in rare-earth monoxides.…”
mentioning
confidence: 99%
“…A technique has been known to substitute a cation with different chemical valence for the host cation in the oxide in order to change the chemical valence of the transition metal ion. The technique has quite often been used in the researches for the superconducting oxides, e.g., M x La 2Àx CuO 4Ày (M = Ba, Sr, Ca, Na) (1)(2)(3) and Ce x Ln 2Àx CuO 4Ày (Ln = Pr, Nd, Sm, Eu) (4)(5)(6). In these cases, La 2 CuO 4 and Ln 2 CuO 4 (Ln = Pr, Nd, Sm, Eu) are called the Mott insulator (7).…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of the 35K superconducting (La, Ba) 2 CuO 4 compound (Bednorz and Muller, 1986), there has been a great deal of interest in the research of this and related materials. It was found that a substitution of the trivalent La ions by divalent Sr ions in La 2x Sr x CuO 4 (x~0.15) improved the superconducting transition temperatures with T c (onset) above 37K (Kishio et al, 1987;Cava et al, 1987). The La 2 .…”
Section: Introductionmentioning
confidence: 99%